Catalytic Asymmetric Epoxidation of Aldehydes with Two VANOL‐Derived Chiral Borate Catalysts. (7th February 2019) - Gupta, Anil K.; Yin, Xiaopeng; Mukherjee, Munmun; Desai, Aman A.; Mohammadlou, Aliakbar; Jurewicz, Kelsee; Wulff, William D.
Abstract: A highly diastereo‐ and enantioselective method for the epoxidation of aldehydes with α‐diazoacetamides has been developed with two different borate ester catalysts of VANOL. Both catalytic systems are general for aromatic, aliphatic, and acetylenic aldehydes, giving high yields and inductions for nearly all cases. One borate ester catalyst has two molecules of VANOL and the other only one VANOL. Catalysts generated from BINOL and VAPOL are ineffective catalysts. An application is shown for access to the side‐chain of taxol. Abstract : Eine Erzählung von zwei Katalysatoren : Zwei Boratkatalysatoren für die Epoxidierung von Aldehyden mit Diazoacetamiden können aus Bor und VANOL (3, 3′‐Diphenyl‐2, 2′‐bi‐1‐naphthalol) hergestellt werden. Dass diese Katalysatoren unterschiedlich sind, zeigt ein nichtlinearer Zusammenhang der Enantiomerenreinheit des Produkt‐Epoxids gegenüber der von VANOL. Trotz ihrer strukturellen Unterschiede haben beide Katalysatoren ein ähnliches Substratspektrum mit ausgezeichneter asymmetrischer Induktion für verschiedene Aldehyde.